ST-Elevation Magnitude Correlates With Right Ventricular Outflow Tract Conduction Delay in Type I Brugada ECG. (October 2017) - Leong, Kevin M.W.; Ng, Fu Siong; Yao, Cheng; Roney, Caroline; Taraborrelli, Patricia; Linton, Nicholas W.F.; Whinnett, Zachary I.; Lefroy, David C.; Davies, D. Wyn; Boon Lim, Phang; Harding, Sian E.; Peters, Nicholas S.; et al.
Abstract : Background: The substrate location and underlying electrophysiological mechanisms that contribute to the characteristic ECG pattern of Brugada syndrome (BrS) are still debated. Using noninvasive electrocardiographical imaging, we studied whole heart conduction and repolarization patterns during ajmaline challenge in BrS individuals. Methods and Results: A total of 13 participants (mean age, 44±12 years; 8 men), 11 concealed patients with type I BrS and 2 healthy controls, underwent an ajmaline infusion with electrocardiographical imaging and ECG recordings. Electrocardiographical imaging activation recovery intervals and activation timings across the right ventricle (RV) body, outflow tract (RVOT), and left ventricle were calculated and analyzed at baseline and when type I BrS pattern manifested after ajmaline infusion. Peak J-ST point elevation was calculated from the surface ECG and compared with the electrocardiographical imaging–derived parameters at the same time point. After ajmaline infusion, the RVOT had the greatest increase in conduction delay (5.4±2.8 versus 2.0±2.8 versus 1.1±1.6 ms; P =0.007) and activation recovery intervals prolongation (69±32 versus 39±29 versus 21±12 ms; P =0.0005) compared with RV or left ventricle. In controls, there was minimal change in J-ST point elevation, conduction delay, or activation recovery intervals at all sites with ajmaline. In patients with BrS, conduction delay in RVOT, but not RV or left ventricle, correlated to the degree of J-ST point elevation (Pearson R, 0.81; P <0.001). No correlation was found between J-ST point elevation and activation recovery intervals prolongation in the RVOT, RV, or left ventricle. Conclusions: Magnitude of ST (J point) elevation in the type I BrS pattern is attributed to degree of conduction delay in the RVOT and not prolongation in repolarization time.